The pharmacological treatment of chronic comorbidities in COPD: mind the gap!. (August 2018) - Vespasiani-Gentilucci, Umberto; Pedone, Claudio; Muley-Vilamu, Moises; Antonelli-Incalzi, Raffaele
Abstract: Background: Chronic obstructive pulmonary disease (COPD) is commonly associated with other chronic diseases, which poses several diagnostic and therapeutic problems. Indeed, important comorbidities frequently remain unrecognized and, then, untreated, whereas respiratory drugs may have non respiratory side effects, and selected non respiratory drugs may variably affect the respiratory function. Objective: to describe: how COPD affects the presentation and contributes to the diagnostic challenges of its most common comorbidities; how coexisting COPD impacts the therapeutic approach to selected comorbidities and viceversa . Methods: we distinguish comorbidities of COPD depending upon whether they are complications of COPD or share risk factors, mainly smoke, with it or, finally, aggravate COPD. We describe atypical presentations of and diagnostic clues to comorbidities and suggest screening procedures. Finally, the main therapeutic problems, as resulting from the risk of untoward effects of therapies of COPD and its comorbidity, with special attention to drug-drug interactions and possible overdosages, are described. Results: selected complications of COPD, such as osteoporosis, sarcopenia and dysphagia, are rarely recognized and treated, likely due to the poor awareness of them. Important comorbidities, such as coronary artery disease, chronic heart failure, obstructive sleep apnoea syndrome and chronic renal failure, also should be systematically searched for because of their commonly variant presentation. Disease-related symptoms should be distinguished from drug effects or drug-drug interaction effects. Conclusions: a truly comprehensive view of the complex COPD patient, hopefully capitalizing on multidimensional geriatric assessment, is needed to dissect the many components of health status impairment and to provide the optimal care. Selected screening procedures are highly desirable to identify frequently missed comorbidities. Pharmacosurveillance is an essential part of the approach to COPD and its comorbidities.